Repression of CYSTATHIONINE γ-SYNTHASE in Seeds Recruits the S-Methylmethionine Cycle. Issue 3 (23rd May 2017) - Cohen, Hagai; Hacham, Yael; Panizel, Irina; Rogachev, Ilana; Aharoni, Asaph; Amir, Rachel
Abstract : The S-methylmethionine cycle in vegetative and reproductive tissues supports methionine metabolism in developing Arabidopsis seeds when its synthesis through the aspartate family pathway is restricted. Abstract: S -Methylmethionine (SMM ) was suggested previously to participate in the metabolism of methionine (Met) in seeds. To further reveal its roles, we had previously produced transgenic Arabidopsis ( Arabidopsis thaliana ) RNA interference (RNAi ) seeds with lower transcript expression of CYSTATHIONINE γ-SYNTHASE ( AtCGS ), Met's main regulatory enzyme. Unexpectedly, these seeds accumulated significantly higher levels of Met compared with control seeds through an as yet unknown mechanism. Here, transcript and metabolic analyses coupled with isotope-labeled [ 13 C]SMM and [ 13 C]Met feeding experiments enabled us to reveal that SMM that was synthesized in rosette leaves of RNAi plants significantly contributed to the accumulation of Met in their seeds at late stages of development. Seed-specific repression of AtCGS in RNAi seeds triggered the induction of genes operating in the SMM cycle of rosette leaves, leading to elevated transport of SMM toward the seeds, where higher reconversion rates of SMM to Met were detected. The metabolic rearrangements in RNAi seeds resulted in an altered sulfur-associated metabolism, such as lower amounts of Cys and glutathione, as well as a differential composition of glucosinolates. Together, the data propose a novel cross talk existing between seeds and rosette leaves along with mutual effects between the Asp family and SMM pathways operating in these tissues. They also shed light on the effects of higher Met levels on seed physiology and behavior.